Spatial organisation and socio-cultural basis of traditional courtyard houses - Chang, Simon Shieh-Haw (University of Edinburgh, 1986)
The thesis presents a critical analysis of the physical, social and cultural determinants of the traditional Chinese courtyard house. A number of factors which contributed to the stability of the form and spatial arrangement of the courtyard house in traditional China are identified. Early chapters examine the physical and broad social influences upon the form of the courtyard house and explain the different forms of spatial organisation. The discussion then centres on the importance of the Chinese family system and how it was reflected in the spatial arrangement within the house form. The symbol system related to Chinese houses is then considered, paying particular attention to its development from prehistoric China to the Han Dynasty and thereafter, including the concept of Ch'i and the cosmic framework of the Chinese people, which laid the basis for Yang Chai Theory. Ideal residential environments according to the two main Schools of Yang Chai Theory are then described. An example of how the various physical and socio-cultural factors are embodied in an actual courtyard house from the traditional period, taking into account the various elements of Yang Chai Theory, is then illustrated and analysed. The courtyard house reached its demise with the transformation of Chinese societies from agricultural to industrial, as social values and family structure were adjusted to suit the new life-styles. Nevertheless, Yang Chai Theory remains strongly embedded in Chinese culture. The thesis concludes with a discussion of how its components are taken into consideration even nowadays in the forming of residential environments.
The spatial organisation and socio-cultural basis of traditional courtyard houses
Keywords: Anthropology; Folklore; Architecture